2022
DOI: 10.3390/molecules27031037
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolics with Strong Antioxidant Activity from Acacia nilotica Ameliorate Some Biochemical Signs of Arsenic-Induced Neurotoxicity and Oxidative Stress in Mice

Abstract: Neurotoxicity is a serious health problem of patients chronically exposed to arsenic. There is no specific treatment of this problem. Oxidative stress has been implicated in the pathological process of neurotoxicity. Polyphenolics have proven antioxidant activity, thereby offering protection against oxidative stress. In this study, we have isolated the polyphenolics from Acacia nilotica and investigated its effect against arsenic-induced neurotoxicity and oxidative stress in mice. Acacia nilotica polyphenolics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Enayat et al (2012) reported the presence of tannins and polyphenols in A. nilotica pods extract. In a recent study, Foyzun et al (2022) have reported 256.752±10.086 mg GAE/g of total phenolic content in crude methanol extract of A. nilotica pods which appeared very close to those obtained in our study (257.61±4.22 mg GAE/g). However, the content of flavonoids was found with much higher content when compared to the earlier cited research works.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Enayat et al (2012) reported the presence of tannins and polyphenols in A. nilotica pods extract. In a recent study, Foyzun et al (2022) have reported 256.752±10.086 mg GAE/g of total phenolic content in crude methanol extract of A. nilotica pods which appeared very close to those obtained in our study (257.61±4.22 mg GAE/g). However, the content of flavonoids was found with much higher content when compared to the earlier cited research works.…”
Section: Discussionsupporting
confidence: 91%
“…Similar result was reported by Alsiddig et al (2015), where the ethanol extract of A. nilotica pods was able to scavenge the DPPH with 93%. Also, from the results published by Foyzun et al (2022), it was highlighted that at 12.5 µg/mL concentration, methanol extract of A. nilotica pods was able to strongly scavenge the DPPH. With the ABTS and H 2 O 2 radical scavenging methods, the methanol extract of A. nilotica pods was found to significantly scavenge free radical in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, several preclinical and clinical studies support the potential functional and nutraceutical use of A. nilotica , owing to its diversified phytochemistry and bioactivities (Abduljawad, 2020 ; Saeedi et al., 2020 ). This plant's polyphenolic extract reportedly helps reduce induced neurotoxicity and oxidative stress conditions in an animal model (Foyzun et al., 2022 ). Moreover, A. nilotica extract restored glucose homeostasis by inhibiting JNK (c‐Jun N‐terminal kinase) and upregulation of insulin (Majeed et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports on plant-derived compounds such as polyphenolics, alkaloids and other plant extracts proclaim plants as unrealized source of antimicrobial agents ( Othman et al, 2019 ). However, a good number of polyphenolics, alkaloids and flavonoids reported from different plants are still awaiting to be tested for their antimicrobial activity ( Ahammed et al, 2021 , Islam et al, 2021 , Al-Amin et al, 2022 , Foyzun et al, 2022 , Mustafa et al, 2022 , Pawar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%